2016
DOI: 10.1111/jpn.12481
|View full text |Cite
|
Sign up to set email alerts
|

Energy requirements of early‐weaned Dorper cross‐bred female lambs

Abstract: The net and metabolizable energy (NE and ME) requirements of Dorper cross-bred female lambs with BWs of 20-35 kg were assessed in a comparative slaughter trial. Thirty-five Dorper × thin-tailed Han cross-bred female lambs weaned at ~50 days of age (20.3 ± 2.15 kg BW) were used. Seven randomly selected lambs were slaughtered at the start of the trial (baseline group). An intermediate group consisting of seven randomly selected lambs fed ad libitum was slaughtered when the lambs reached an average BW of 28.5 kg.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…The dataset used in the present study was obtained from 159 lambs in seven energy metabolism studies undertaken as part of the National Technology Program for the Meat Sheep Industry of China from 2010 to 2015 [1720,25–27]. The animals were offered pelleted diet in all studies with concentrate:forage ratio ranging from 12:88 to 92:8.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dataset used in the present study was obtained from 159 lambs in seven energy metabolism studies undertaken as part of the National Technology Program for the Meat Sheep Industry of China from 2010 to 2015 [1720,25–27]. The animals were offered pelleted diet in all studies with concentrate:forage ratio ranging from 12:88 to 92:8.…”
Section: Methodsmentioning
confidence: 99%
“…With the introduction of Dorper sheep from Australia in 2001 [16], Dorper sheep×thin-tailed Han crossbred sheep has become a predominant breed for meat-producing in China. In recent years, the nutrient requirements of Dorper×thin-tailed Han crossbred sheep in terms of energy [1720], protein [2123], and minerals [24] have been extensively studied and reported. Based on those conditions, dataset used in the current study to provide basic CH 4 emission parameters were obtained from the same breed (Dorper×thin-tailed Han), feeding conditions (confined indoors), and feeding regime (pelleted diet), which largely mirrors the current characteristics of sheep production system in China.…”
Section: Introductionmentioning
confidence: 99%
“…Beef cattle feeding systems that do not meet the energy requirements of the animals may result in the failure of livestock to meet performance expectations [ 1 , 2 ]. The major reasons for low productivity in tropical developing countries are the genetic potential of the animals, the available feeds and the feeding systems, which depend on rice straw or other low-quality crop by-products and thus limit feed intake and digestion, productivity and environmental sustainability [ 3 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the intensive livestock industry, protein is commonly the most expensive feed component and therefore, it is necessary to have a precise understanding of protein requirement of livestock not only to ensure farm profitability, but also to help reduce nitrogen (N) emission to the environments [ 1 ]. Modern feeding systems, such as Agricultural and Food Research Council (AFRC) [ 2 ], Commonwealth Scientific and Industrial Research Organisation (CSIRO) [ 3 ], and National Research Council (NRC) [ 4 ], have reported protein and other nutrient requirements of sheep, which are widely adopted for diet formulation in the world.…”
Section: Introductionmentioning
confidence: 99%